Historical memory and history taught: symbolic constructs of prospective teachers and their link to school experience (Tempo e Argumento, 2021)
Historical memory and recent history are concepts increasingly more present in classrooms and more consolidated in historiography, being a relevant issue in the building of post-transitional democratic societies. However, in the classroom, it is still a field that requires more accurate research on some elements that help to better understand its incorporation in the didactic process. This article analyzes the symbolic constructs of prospective teachers regarding memory and outlines a link to their school experience, particularly to the narratives found in textbooks, as the main didactic resource. The aim is contributing to the debate between history taught and history inquired into. The research, which has taken a hermeneutic tone, addresses the conceptualizations and the role assigned to memory by prospective teachers, related to the role played by textbooks starting from information collected by using a questionnaire built on purpose and the narratives found in textbooks, which have conveyed an inaccurate and partial view of memory. Thus, we highlight the need to rethink the relationship between recent history and memory from a didactic viewpoint, both in textbooks and in early teachers training.Keywords: historical memory; history taught; textbook; conceptualizations; prospective teachers.